Enhancement of Lithium Niobate nanophotonic structures via spin-coating technique for optical waveguides application - Fakhri Makram A.; Wahid M.Halim A.; Badr Ban A.; Kadhim Suad M.; Salim Evan T.; Hashim Uda; Salim Zaid T. (EPJ Web of Conferences, 2017)
This work is dedicated to investigation of temperature effects in Lithium Niobate (LiNbO3) nanostructures. The LiNbO3 nanostructures were deposited on glass substrate by spin-coating technique. LiNbO3 was set down at 3000 rpm for 30 sec and annealed from 100 to 600 °C. The structures were characterized and analyzed by scanning electron microscopy (SEM) and ultra-violet visible (UV-vis) spectrophotometer. The measured results have showed that by increasing annealing temperatures, the structures start to be more crystallized and be more homogenized until the optimum arrangement was achieved. Once this was accomplished, it's applicable for optical waveguides development. Eventually, it starts to be less crystallization and non-homogeneous. Energy gap was recorded to be at average value of 3.9 eV.